2020
DOI: 10.3389/fpsyt.2020.582352
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life and Self-Control Buffer Stress in Times of COVID-19: Moderating and Mediating Effects With Regard to Mental Distress

Abstract: Background As evidenced by several studies, mental distress increased substantially during the COVID-19 pandemic. In this period, citizens were asked to exercise a high degree of self-control with regard to personal and social health behavior. At the same time, we witnessed an increase of prosocial acts and shared creative expressions, which are known to serve as sources of meaning. Meaning in life and self-control are acknowledged psychological resources. Especially in times of crisis, meaning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
187
1
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(229 citation statements)
references
References 91 publications
(130 reference statements)
27
187
1
14
Order By: Relevance
“…The extant literature emphasizes that satisfaction and meaning in life are associated with reduced psychological distress related to COVID-19 and increased emotional well-being (Schnell and Krampe, 2020 ; Tomaszek and Muchacka-Cymerman, 2020 ). Subsequently, in the present study, satisfaction with life and search for meaning in life were found to be significantly and positively correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature emphasizes that satisfaction and meaning in life are associated with reduced psychological distress related to COVID-19 and increased emotional well-being (Schnell and Krampe, 2020 ; Tomaszek and Muchacka-Cymerman, 2020 ). Subsequently, in the present study, satisfaction with life and search for meaning in life were found to be significantly and positively correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Since meaning in life is a resource the helps people cope with stress, uncertainty, anxiety, and trauma it may also play a vital role in helping communities and the broader society face collective threats and challenges. Recent studies, for instance, found that higher meaning in life is associated with lower levels of anxiety and COVID-19 stress (Trzebinski et al, 2020 ) and lower levels of mental distress among those facing pandemic-related stress (Schnell and Krampe, 2020 ). In order to successfully respond to and recover from collective threats such as pandemics, economic recessions, and natural disasters, humans need to possess the psychological fortitude that not only helps them manage their personal anxieties, but that also drives them to want to positively contribute to the world around them.…”
Section: Using Meaning To Overcome Major Societal Threats and Challenmentioning
confidence: 99%
“…Schnell and Krampe ( 2020 ) confirm that meaning-in-life questions have increased during the pandemic—particularly through prosocial acts and creative expressions. The creation of meaning in life can be viewed as a psychological resource, and people with high levels of meaningfulness are viewed as more hopeful, optimistic, and stress-resistant, while people with low levels of meaning are usually threatened by loss of identity, suicide, higher levels of pain and suffering and aggravated distress during the pandemic (Ali and Lalani, 2020 ).…”
Section: The Meaning Of Camus In Times Of Covid-19mentioning
confidence: 99%